The Effect of Service Quality, Brand Image, E-WOM, Customer Satisfaction on Customer Loyalty - Sahlani Sahlani; Endang Ruswanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Service quality has become an important strategy in business that encourages customer involvement in creating products that meet customer demand to create customer satisfaction. Brand Image and E-WOM are also still important considerations that influence customer satisfaction. With customer satisfaction, it will be a factor in customer loyalty. The purpose of this study is to identify the effect of service quality, brand image, E-WOM, and customer satisfaction on loyalty in the Jabodetabek fashion industry. This study was designed using a purposive sampling method involving 180 customers who had purchased from several store brands in Jabodetabek malls. Data were analyzed using the Structural Equation Model (SEM), with SmartPLS 4.0. Some of the findings in this study are that service quality, brand image, and E-WOM affect customer loyalty and service quality also has a direct effect on customer loyalty, while E-WOM and customer satisfaction do not affect customer loyalty. The managerial implications of this study are that although in general customer satisfaction contributes to loyalty, this relationship is not always simple and certain. In a competitive market like Jabodetabek with international fashion brands, other factors such as price, trends, and brand awareness also play an important role in determining customer loyalty.